Study on the Scale-Up Possibility of a Combined Wet Grinding Technique Intended for Oral Administration of Meloxicam Nanosuspension - Csilla Bartos; Anett Motzwickler-Németh; Dávid Kovács; Katalin Burián; Rita Ambrus (Pharmaceutics)
Background/Objectives: This article reports on the scalability of a combined wet grinding technique applying planetary ball mill and ZrO2 pearls as the grinding medium. After the determination of the parameters in a laboratory scale, the tenfold scale-up method was set. Meloxicam (MEL) was used as a nonsteroidal anti-inflammatory drug (NSAID) intended for per os delivery. During grinding, the PVA solution was used as a dispersion medium. Methods: The influence of the scaling-up on the particle size, morphology, crystallinity, and intra- and interparticulate phenomena has been studied. Formulation investigations of the milled suspensions were carried out. The dissolution test and the cytotoxicity analyses were accomplished. Results: Submicron MEL particle-containing samples were produced in both grinding scales. After the particle size determination was achieved from the suspensions, the wet milled, dried products were studied. The particle size of the dried products fell into the same range for both scales of milling (the maximum particle size was about 580 nm). There was no significant difference in drug crystallinity after the grindings; 70% of MEL remained crystalline in both cases. A remarkable interaction between the components did not develop as a result of milling. The polarity of the products increased, which resulted in a better dissolution, especially in the case of intestinal fluid (~100% in the first 5 min). The products were not found to be toxic. Conclusions: This research demonstrates that the scaling-up of combined wet grinding technique is feasible by adjusting the milling parameters and the adequate amount of excipient.